Student Leaders’ Assessment on RA 11462 in Nueva EcijaStudent Leaders’ Assessment on RA 11462 in Nueva Ecija - Nabong, Dessalin R. (International Journal of Humanities and Education Development (IJHED), 2020)
In the Philippines, local government serves as the foundation of the entire structure of the government. The study described the social, economic, and political impact of RA 11462. Also, the study described the relationship and difference between and among the socio-demographic profile and social, political and economic impact of RA 11462. Using quantitative research, the profile characteristics of the selected student leader-respondents from the two sample universities in Cabanatuan City, and their assessment of the social, economic and political impact of the term extension of the Barangay and SK members will describe quantitatively. A total 150 student leaders (75 from public school and 75 from private school) in Nueva Ecija were involved in this study. Based from the gathered data, it can be noted that most of the respondents were undecided regarding the positive or negative social, economic and political impact of RA 11462. It implies that the impact of RA 11462 has an equilibrium on both positive and negative. It is recommended to have the government improve the response to have more positive impact than negative impact in terms of social, economic, political removing neutrality. The null hypotheses are retained. It implies that socio-demographic profile of the respondents does not affect the social, economic and political impact of RA 11462. However, the position currently held affect the social impact of RA 11462. Thus, the null hypothesis for social impact is rejected. It is recommended to have a deepen research on other independent variables such mentioned on this study did not affect any social, economic and political impact of R.A. 11462. However, it should be noted that the position currently held affect social impact of RA 11462. It is recommended then to have further research on factors affected by the independent variable.